Preventing Human Trafficking: Between Facts and Problems, A Book Review “Pencegahan Tindak Pidana Perdagangan Orang” by Libby SinlaEloE & Paul SinlaEloE, Libby SinlaEloE and Paul SinlaEloE, Rumah Perempuan, 2017, 50 pages, ISBN 978-602-50912-1-6 - Widowati, Arrum (JILS (Journal of Indonesian Legal Studies), 2021)
The author begins their writing by describing the article on Prevention of Criminal Trafficking in Persons (TPPO) which is a joint obligation between the Government, Regional Government, the community, and the family. That is the mandate in Article 57 paragraph (1) of the Act of the Republic of Indonesia Number 21 of 2007, concerning Eradication of Criminal Acts of Trafficking in Persons (UUPTPPO). This book consists of 3 parts, namely: Understanding the Criminal Acts of Trafficking in Persons, Prevention of Trafficking in Persons Act Version of Law Number 21 of 2007, Prevention of Community-Based Trafficking in Persons.